Essentials of business statistics (McGraw Hill, 2012)
The new edition of Essentials of Business Statistics delivers clear and understandable explanations of core business statistics concepts, making it ideal for a one-term course in business statistics. The author team emphasize the importance of interpreting statistical results to make effective decisions to improve business processes. The text offers real applications of statistics that are relevant to today's business students which can be seen in the continuing case studies throughout the book. Continuing cases span throughout a chapter or even groups of chapters, easing students into new topic areas